Use of personal protective equipment to protect against respiratory infections in Pakistan: A systematic review - Abrar Ahmad Chughtai; Wasiq Khan (Elsevier, 2020)
Like other low-income countries, limited data are available on the use of personal protective equipment (PPE) in Pakistan. We conducted a systematic review of studies on PPE use for respiratory infections in healthcare settings in Pakistan. MEDLINE, Embase and Goggle Scholar were searched for clinical, epidemiological and laboratory-based studies in English, and 13 studies were included; all were observational/cross-sectional studies. The studies examined PPE use in hospital (n = 7), dental (n = 4) or laboratory (n = 2) settings. Policies and practices on PPE use were inconsistent. Face masks and gloves were the most commonly used PPE to protect from respiratory and other infections. PPE was not available in many facilities and its use was limited to high-risk situations. Compliance with PPE use was low among healthcare workers, and reuse of PPE was reported. Clear policies on the use of PPE and available PPE are needed to avoid inappropriate practices that could result in the spread of infection. Large, multimethod studies are recommended on PPE use to inform national infection-control guidelines. Keywords: Respiratory tract infections, Influenza, Infection control, Personal protective equipment, Health personnel, Pakistan